KINERJA KEUANGAN PEMERINTAH KOTA DI JAWA TIMUR - Avicenna Asyifyan, Mirza (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Regional autonomy gives birth to independence, where a regional government is required to realize its high-performance government. The purpose of this study is to analyze the financial independence of city governments in East Java Province. Using panel data sourced from the Directorate General of Fiscal Balance, Ministry of Finance of the Republic of Indonesia for 2013-2022. The research approach is quantitative with a descriptive research type. With the analysis of One-Sample Test data, this study is also directed to test the hypothesis, namely: the financial independence of city governments in East Java Province is 1.5 (low). The results of the study found that the research hypothesis was tested so that within the observation period or period, the financial capacity of city governments in East Java was in a low position with a constructive relationship pattern.